Digital Expert System for Geoinformation Support To Hard Areas Large Wildfires Management - Evgeniy A. BAIKOV; Valery M. ABRAMOV; Vladimir A. BOLSHAKOV; Sergey V. LUKYANOV; Yuri Yu. SMIRNOV; Oksana PETRIEVA; Alexander S. AVERKIEV; Mikhail B. SHILIN; Igor A. SIKAREV; Oleg I. SHEVCHUK (Communications of International Proceedings, 2021)
Considered expert system development for geoinformation support to large wildfires in hard areas management within Industry 4.0 period under conditions of climate change and COVID-19. The study uses environmental risk management fundamentals, web-technologies and the databases constructing methods. As research result, it is recommended remote sensing and modelling data using within geoinformation support expert systems to increase the efficiency of wildfires management. As instruments, it is proposed the modular expert systems which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks. As study results, some examples of developed expert system using are demonstrated. The presented in article research results have significant scientific novelty and can be useful for wildfire mitigation in environment. Platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for discussion and data exchange during research.
Keywords: expert system; geoinformation support; large wildfires management; hard areas